2012
DOI: 10.4186/ej.2012.16.3.123
|View full text |Cite
|
Sign up to set email alerts
|

The Monitoring of H2S and SO2 Noxious Gases from Industrial Environment with Sensors Based on Flame-Spray-Made SNO2 Nanoparticles

Abstract: Abstract. The noxious gas sensors were developed successfully using flame-spray-made SnO2 nanoparticles as the sensing materials. The functionalized nanoparticle properties were further analyzed by XRD, BET and TEM analyses. The SnO2 nanoparticles (SSABET: 141.6 m 2 /g) were investigated revealing non-agglomerated spherical, hexagonal, rectangle (3-10 nm), and rod-like (3-5 nm in width and 5-20 nm in length) morphologies. The sensing films were prepared by spin coating onto the Al2O3 substrates interdigitated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
1
9
0
Order By: Relevance
“…The lm was able to detect 16 ppb [(R g À R a )/R a  100 ¼ 26%] NO 2 concentration, which was comparatively low concentration than that reported in other studies. 40,41 Moreover, the WO 3 lm shows a linear response to different NO 2 concentration in the 16-800 ppb range and a detection resolution of 11 ppb for the optimum operating temperature (150 C) with help of impulsive mode of temperature. Theoretically estimated LOD is 1.6 ppb obtained from the linear t of response data of lm shown in inset of Fig.…”
Section: Nitrogen Dioxide (No 2 ) Sensing Characteristics Of the Wo 3mentioning
confidence: 98%
“…The lm was able to detect 16 ppb [(R g À R a )/R a  100 ¼ 26%] NO 2 concentration, which was comparatively low concentration than that reported in other studies. 40,41 Moreover, the WO 3 lm shows a linear response to different NO 2 concentration in the 16-800 ppb range and a detection resolution of 11 ppb for the optimum operating temperature (150 C) with help of impulsive mode of temperature. Theoretically estimated LOD is 1.6 ppb obtained from the linear t of response data of lm shown in inset of Fig.…”
Section: Nitrogen Dioxide (No 2 ) Sensing Characteristics Of the Wo 3mentioning
confidence: 98%
“…Although the volume of the literature is remarkable, most of the works are devoted to semiconducting oxides and the operation temperatures of these sensors have been reported from only room temperature to 300 • C. One of the few papers describing sensing H 2 S at higher temperatures was completed by Dawson et al; they utilized a Cr 2-y Ti y O 3+x sensing composition for a resistive-type sensor design [18] The material demonstrated a p-type characteristic at elevated temperatures (>250 • C) and showed an increase in resistance upon exposure to H 2 S (50 ppm) within a testing range of 250-500 • C. It is the sole paper, at least to our knowledge in literature, that provided temperature desorption curves for both SO 2 and H 2 S. It was seen that H 2 S exhibited two maxima at about 150 • C and 470 • C; however, the loss of SO 2 from the surface occurred at 470 • C. It was concluded that a sensor that operates at 350 • C can be cleaned by heat treatment, and a pre-treatment will increase the sensor response of the sensor [18] Some of the other transition metal oxides demonstrated for H 2 S sensing are as follows: PdO x , WO 3 , MoO 3 , In 2 O 3 , CeO 2 , SnO 2 , TiO 2 , ZnO, CuO, CdO, and various ferrites [10,15,[19][20][21][22][23][24][25][26] A majority of these reports are based on WO 3 compositions [8,10,15,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] In the current work, tungstate and molybdate compositions were investigated as alternative sensing materials to the typical binary compositions for sulfur gas species at higher testing temperatures (≥600 • C). Tungstates and molybdates are known to be wide band gap oxide semiconductors (3-5 eV).…”
Section: Introductionmentioning
confidence: 99%
“…Recent developments, for example, include SO 2 gas detector utilizing SnO 2 nanoparticles as sensing elements [3] and ZnObased nanostructured nitrogen dioxide sensor [4]. While sensitive, one drawback is that these sensors only operate at temperatures higher than 200°C.…”
Section: Introductionmentioning
confidence: 99%